32 The impact of a rapid access nurse led pre-operative cardiac rhythm assessment service in a regional tertiary centre. (June 2018) - Chapman, Michael; Mudd, Jayne; Hall, Angela; Theakston, Ashley; Rice, Tony; Owen, Jane; Wyatt, Clair; Daniell, Annette; Turley, Andrew; Linker, Nick
Abstract : Introduction: Cardiac arrhythmias including atrial fibrillation (AF) are common affecting 3% of adults. The main prognostic concern relates to stroke risk: 33% of patients experiencing an ischaemic stroke have AF. Pre-operative AF is an independent predictor of peri-operative stroke and 2% of patients with AF suffer a stroke between diagnosis and initiation of anticoagulation. To reduce peri-operative risk, patients are often referred for outpatient cardiovascular assessment prior to surgery. Non-specific ECG changes, AF and anti-coagulation management account for 19% of referrals from surgery. Referral delays surgery and 61% of patients require no immediate intervention. We describe an open access rapid cardiovascular assessment service for patients attending pre-operative assessment clinic in a tertiary cardiovascular centre aiming to avoid delays in surgery, minimise surgical risk and optimise long-term management. Methods: Our open access, same day service was initiated in December 2015 and is ran by a team of cardiac rhythm management specialist nurses. Referrals are accepted from adult surgical pre-assessment clinics within our trust. Data was collected between December 2015 and November 2017. Results: 83 patients were referred: mean age 73.3 (SD 9.99) years and 72% male. Indications for referral are summarised in table one. All patients with a new diagnosis of AF/atrial flutter had a stroke risk assessment (CHADS-VASc). CHADS-VASc >2 females or >1 males were offered anticoagulation unless contraindicated (n=1 haematuria n=1 alcohol dependency). 97% patients with AF/flutter had assessment of rate control and 90% with new AF were referred for echocardiography. 86% of patients with known AF were referred due to rapid ventricular response. All patients with sinus node or AVN disease were investigated with a cardiac monitor (n=4) or offered permanent pacing (n=4, 2 CHB, 22nd degree AV block). Both patients with complete heart block were admitted on the day of assessment for pacemaker implantation. Following ambulatory monitoring, both patients with sinus node disease and one patient with AVN disease did not require pacing. One patient had an accessory pathway identified and underwent electrophysiology testing within 7 days confirming a low-risk pathway. All 6 patients with ectopy had ambulatory monitoring and intervention was not required. As patients were seen on the same day as referral, there was a significant reduction in wait when compared to routine cardiology outpatient assessment (mean 34 days). Conclusion: Pre-operative assessment provides an opportunity for screening for cardiovascular disease. This service allows for rapid assessment, initiation of anticoagulation, prompt pacing where required and reduces unnecessary delays in surgery.